Professor Ray Jackendoff officially receives the Merrin Chair in the ASEAN Auditorium. Photo 117 - Leonard, Spencer (Tufts Archival Research Center, 2008)
Professor Ray Jackendoff officially receives the Merrin Chair in the ASEAN Auditorium.